2004
DOI: 10.1007/s00493-004-0009-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Mechanical Algorithms for the Nonabelian Hidden Subgroup Problem

Abstract: We give a short exposition of new and known results on the "standard method" of identifying a hidden subgroup of a nonabelian group using a quantum computer. AbstractWe give a short exposition of new and known results on the "standard method"of identifying a hidden subgroup of a nonabelian group using a quantum computer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
119
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(121 citation statements)
references
References 9 publications
2
119
0
Order By: Relevance
“…It is shown in [11] that sampling the row index in the strong standard method provides no additional information. They also show that the additional information provided by the strong method in a random basis scales with 3 p jH j 2 k.G/=jGj where k.G/ is the number of conjugacy classes of the group G and jH j the size of the hidden subgroup.…”
Section: Definition 2 the Standard Methods Of Quantum Fourier Samplinmentioning
confidence: 99%
See 2 more Smart Citations
“…It is shown in [11] that sampling the row index in the strong standard method provides no additional information. They also show that the additional information provided by the strong method in a random basis scales with 3 p jH j 2 k.G/=jGj where k.G/ is the number of conjugacy classes of the group G and jH j the size of the hidden subgroup.…”
Section: Definition 2 the Standard Methods Of Quantum Fourier Samplinmentioning
confidence: 99%
“…They also show that the additional information provided by the strong method in a random basis scales with 3 p jH j 2 k.G/=jGj where k.G/ is the number of conjugacy classes of the group G and jH j the size of the hidden subgroup. Both [14] and [11] show that hidden subgroups of S n of size jH j D 2, generated by involutions with large support, cannot be distinguished from identity; exactly the task that needs to be solved for Graph Automorphism. Recently, [29] have essentially shown that the strong standard method cannot distinguish the subgroup generated by a fixed point free involution from identity.…”
Section: Definition 2 the Standard Methods Of Quantum Fourier Samplinmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible to improve the success probability to one for Abelian groups of smooth order [4] (a group is of c-smooth order if all prime factors of |G| are at most (log |G|) c for some constant c). For non-Abelian groups, our knowledge is much more limited [5,6,7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…An important predecessor is Simon's algorithm [23] for the case G = (Z/2) n . Shor's algorithm extends to the general abelian case [14], to the case when H is normal [10], and to the case when H has few conjugates [9]. Since the main step in the generalized algorithm is the quantum character transform on the group algebra C[G], we will call it the character algorithm.…”
Section: Introductionmentioning
confidence: 99%